Given a function f ( x ) = ( 6 0 0 7 3 − x 1 0 ) 1 0 1 and f ′ ( 2 ) = f ′ ( a ) 1 , where a is a positive integer.
Find a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I say this is a lovely sum
Log in to reply
very nyc problem
Wonderful sum
I did it the long way, got 59049^(1/10) which simplified to 3. Nice question.
( f − 1 ) ′ ( f ( x ) ) = f ′ ( x ) 1
( f − 1 ) ′ ( f ( 3 ) ) = f ′ ( 2 )
a = 3
Problem Loading...
Note Loading...
Set Loading...
Note that f ( f ( x ) ) = x
f ′ ( x ) = f ′ ( f ( x ) ) 1
f ′ ( 2 ) = f ′ ( f ( 2 ) ) 1
f ( 2 ) = 3 = a